John Mason Potter Correspondence - Potter, John Mason, 1907-; Jacob, Hilda McLeod; Maine State Library (Digital Maine, 2015)
Entries include brief biographical information, typed biographies, years of typed and handwritten worldwide correspondence with the Maine State library on hotel and personal stationery -- from The Cunard Queen Elizabeth 2, India, and Greenland, a print advertisement with a biography, a Borderguard small press association pamphlet featuring Bern Porter Books, newspaper clippings in many languages with the photographic images of Porter with his brother -- wherein Porter is considering the establishment of a Maine Institute for Thinking, of Porter with his wife in Russia, and Porter, his wife and manager Pacheco in Costa Rica, a photograph of Porter, a sublunary handwritten message with a TEAM, Inc., pamphlet, a newspaper clipping concerning Newfoundland vocabulary, a publisher review tear sheet, a typed letter from editor Cronberger of Who's Who in Space concerning Porter's selection in a time capsule, artwork, a postcard from Maine with Porter's rented house circled, a typed yearly journal, a press release on Colby College stationery, a performance art flyer, and correspondence concerning the upcoming dedication ceremony for the State of Maine, Cultural Building.